The research priorities of patients attending UK cancer treatment centres: findings from a modified nominal group study - Corner, J (Nature Publishing Group, 2007)
Members of the public are increasingly consulted over health care and research priorities. Patient involvement in determining cancer research priorities, however, has remained underdeveloped. This paper presents the findings of the first consultation to be conducted with UK cancer patients concerning research priorities. The study adopted a participatory approach using a collaborative model that sought joint ownership of the study with people affected by cancer. An exploratory, qualitative approach was used. Consultation groups were the main method, combining focus group and nominal group techniques. Seventeen groups were held with a total of 105 patients broadly representative of the UK cancer population. Fifteen areas for research were identified. Top priority areas included the impact cancer has on life, how to live with cancer and related support issues; risk factors and causes of cancer; early detection and prevention. Although biological and treatment related aspects of science were identified as important, patients rated the management of practical, social and emotional issues as a higher priority. There is a mismatch between the research priorities identified by participants and the current UK research portfolio. Current research activity should be broadened to reflect the priorities of people affected by the disease.